Gesundes Kinzigtal Integrated Care: improving population health by a shared health gain approach and a shared savings contract - H. Hildebrandt; C. Hermann; R. Knittel; M. Richter-Reichhelm; A. Siegel; W. Witzenrath (International Journal of Integrated Care, 2010)
Introduction: Integrated care solutions need supportive financial incentives. In this paper we describe the financial architecture and operative details of the integrated pilot Gesundes Kinzigtal. Description of integrated care case: Located in Southwest Germany, Gesundes Kinzigtal is one of the few population-based integrated care approaches in Germany, organising care across all health service sectors and indications. The system serving around half of the population of the region is run by a regional health management company (Gesundes Kinzigtal GmbH) in cooperation with the physicians' network in the region (MQNK), a German health care management company with a background in medical sociology and health economics (OptiMedis AG) and with two statutory health insurers (among them is the biggest health insurer in Southwest Germany: AOK Baden-Württemberg). Discussion and (preliminary) conclusion: The shared savings contract between Gesundes Kinzigtal GmbH and the two health insurers, providing financial incentives for managers and health care providers to realize a substantial efficiency gain, could be an appropriate contractual base of Gesundes Kinzigtal's population health gain approach. This approach is based on the assumption that a more effective trans-sector organisation of Germany's health care system and increased investments in well-designed preventive programmes will lead to a reduction in  morbidity, and in particular to a reduced incidence and prevalence of chronic diseases. This, in turn, is to lead to a comparative reduction in health care cost. Although the comparative cost in the Kinzigtal region has been reduced from the onset of Gesundes Kinzigtal Integrated Care, only future research will have to demonstrate whether - and to what extent - cost reduction may be attributed to a real population health gain.